THE TREATMENT DISPENSED TO THE TYPICAL FOREST OF THE ATLANTIC FOREST BIOME INSERTED IN THE CERRADO BIOME - Serrano, Alessandra Marques (Floresta, 2022)
The study aimed to discuss the protection given to forest formations typical of the Atlantic Forest biome inserted in the Cerrado biome and to identify the protective and normative commands to be observed when the suppression of this vegetation is authorized. The methodological option was for a literature survey, in exploratory and explanatory modalities, with a qualitative approach. The studies were carried out in articles and in norms dedicated to the Atlantic Forest and Cerrado biomes. The study of the Atlantic Forest covered the Brazilian territory and the study of the Cerrado biome, as it respects general rules for the protection of native vegetation, was limited to the states of São Paulo and Minas Gerais, which have specific protection rules. From the researched, it was observed that the protection given to the vegetation inserted in the Atlantic Forest biome through Law n°. 11,428, of 2006, extends to the vegetation inserted in the Cerrado biome when it is characterized as typical forest formations of the Atlantic Forest biome, considering, mainly, the exposed in the Federal Constitution of 1988, which recognizes the Atlantic Forest as a national heritage and its use must ensure the conservation of the environment in which it is inserted. This extension of protection is also justified because the norm creates normative criteria for vegetation wherever it is and not only in the area covered by the Atlantic Forest biome delimited by the map of the Brazilian Institute of Geography and Statistics.